Die multiplen Kapitelle der Pflanzensäulen im Grab des Sennedjem: Zum Phänomen phytoreligiöser Deutungen im Alten Ägypten - Konrad, Kirsten (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
On the northern wall of the tomb chamber of Sennedjem (TT 1) the capitals of the kiosk of the god Osiris are formed of four different flowers - a white and a blue lotus as well as a so called “lily of the south” and a papyrus. These capitals can be interpreted as a phyto-religious symbolization of the four cardinal points. Furthermore, the order of the blossoms symbolizes the daily regeneration of the sun in connection with the yearly inundation of the Nile and is therefore a symbolic guarantee of Egypt’s prosperity.